Rottlerin and Cancer: Novel Evidence and Mechanisms - E. Maioli; C. Torricelli; G. Valacchi (The Scientific World Journal, 2012)
Because cancers are caused by deregulation of hundreds of genes, an ideal anticancer agent should target multiple gene products or signaling pathways simultaneously. Recently, extensive research has addressed the chemotherapeutic potential of plant-derived compounds. Among the ever-increasing list of naturally occurring anticancer agents, Rottlerin appears to have great potentiality for being used in chemotherapy because it affects several cell machineries involved in survival, apoptosis, autophagy, and invasion. The underlying mechanisms that have been described are diverse, and the final, cell-specific, Rottlerin outcome appears to result from a combination of signaling pathways at multiple levels. This paper seeks to summarize the multifocal signal modulatory properties of Rottlerin, which merit to be further exploited for successful prevention and treatment of cancer.